2021
DOI: 10.17583/ijrs.9123
|View full text |Cite
|
Sign up to set email alerts
|

Caught in the Crossfire: LGBT+ Traveller Intersectionality in Post-Brexit Britain

Abstract: This study aimed to investigate a gap in research regarding the contemporary experiences of individuals who identify as both LGBT+ and Traveller through an intersectional lens in post-Brexit Britain. To fully explore this issue three research questions were formulated; Question 1: What are the experiences of individuals that identify with the LGBT+ community and the Traveller community? Question 2: What are the perceptions of Travellers in the LGBTQ+ community? These questions were explored through both qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…While a decade and a half ago, there was a lack of research and data on the status of queer Roma, queer Roma have been gaining visibility at an unprecedented pace. Although queer Roma have barely featured in research on Roma and/or LGBTIQ people, the ever-growing scholarship on queer Roma (Baker, 2003;Kurtić, 2013;Baker, 2015;Máté, 2015Máté, , 2022Corradi, 2017;Fremlova, 2017Fremlova, , 2019Fremlova, , 2021Eminson, 2021;Sartori, 2022) has demonstrated that the lives of queer Roma entail rich, multiple, intersectional experiences stemming from queer Roma's multi-faceted identities. Simultaneously, queer Roma experience intersectional discrimination, marginalisation and multiple objectifications from both non-Roma and Roma.…”
Section: Intersectional Discrimination Experienced By Queer Romamentioning
confidence: 99%
“…While a decade and a half ago, there was a lack of research and data on the status of queer Roma, queer Roma have been gaining visibility at an unprecedented pace. Although queer Roma have barely featured in research on Roma and/or LGBTIQ people, the ever-growing scholarship on queer Roma (Baker, 2003;Kurtić, 2013;Baker, 2015;Máté, 2015Máté, , 2022Corradi, 2017;Fremlova, 2017Fremlova, , 2019Fremlova, , 2021Eminson, 2021;Sartori, 2022) has demonstrated that the lives of queer Roma entail rich, multiple, intersectional experiences stemming from queer Roma's multi-faceted identities. Simultaneously, queer Roma experience intersectional discrimination, marginalisation and multiple objectifications from both non-Roma and Roma.…”
Section: Intersectional Discrimination Experienced By Queer Romamentioning
confidence: 99%